Effects of clear corneal incision location and morphology on corneal surgically induced astigmatism and higher-order aberrations after ICL V4c implantation - Wang, Jun; He, Xiaoying; He, Qin; Han, Jin; Yang, Zixuan; Wang, Xuze; Han, Wei (Frontiers in Medicine, 2024)
To evaluate the effects of clear corneal incision (CCI) location and morphology on corneal surgically induced astigmatism (SIA) and higher-order aberrations (HOAs) in patients receiving implantable collamer lens (ICL V4c) implantation.Methods: This retrospective study classified right eyes that underwent ICL implantation into two groups based on temporal or superior CCI. The Pentacam HR analyzer was used to measure the corneal astigmatism and HOAs. Analysis of the clear corneal incision (CCI) morphology, including incision width (Angle-W), incision length (IL), incision angles (Angle-En/Ex), and distance from the incision to corneal apex (Dis-En/Ex), was conducted using anterior segment optical coherence tomography (AS-OCT).Results: There were 75 eyes in the temporal CCI group and 47 eyes in the superior CCI group. Both groups showed satisfactory safety and efficacy postoperatively. In the temporal CCI group, Dis-En and Dis-Ex were considerably longer, whereas the superior CCI group displayed a significantly wider Angle-W. The anterior and posterior corneal SIA were comparable in both groups. Anterior corneal SIA was significantly correlated to Dis-En and Dis-Ex in the superior CCI group. Superior CCI caused a notable rise in corneal Z (3,3), while temporal CCI led to increased Z (3,1). CCI morphology was correlated to corneal Z (4, -4) and Z (4,4) in the superior CCI group.CCI locations caused slight variations in postoperative corneal SIA and HOAs following ICL implantation. Optimal postoperative visual outcomes may be better achieved with a CCI design featuring an increased distance from the corneal centroid and a decreased Angle-W.